Hyalomma aegyptium: Observed global distribution, imported specimens, preferred hosts and vector competence - Franz Rubel (Ticks and Tick-Borne Diseases)
The tortoise tick Hyalomma aegyptium (Linnaeus, 1758) is a three-host tick, predominantly infesting land tortoises of the genus Testudo. A database was compiled, resulting in 557 H. aegyptium georeferenced locations in the Palearctic. This dataset covers the entire range of H. aegyptium for the first time. Thus, the natural distribution area of H. aegyptium extends from Morocco in northwestern Africa to Kyrgyzstan in Central Asia between 10° W–73° E and 28–46° N, which is shown in an overview map and four detailed maps covering North Africa, the Balkans, the Near East, and the Middle East. In addition, documented findings on land tortoises that have been exported worldwide as popular pets give an impression of the occurrence of H. aegyptium outside its natural distribution. The host species is known from 424 mapped H. aegyptium locations, which can be ranked as follows: 92.9% Testudo spp., 4.0% mammals (mainly hedgehogs and hares), 1.7% humans, 0.9% lizards and 0.5% birds. If only tortoise hosts are considered, these are 92.6% Testudo graeca, 3.8% Testudo hermanni, 2.8% Testudo horsfieldii and 0.8% Testudo marginata. It is striking that no infestation with H. aegyptium has been detected on Testudo kleinmanni in their natural habitat, but it was detected on imported specimens in Malta and the USA. Although numerous tick-borne pathogens have been detected in H. aegyptium, vector competence, i.e. the experimentally proved transmission of pathogens from the vector to the host, could only be demonstrated for three pathogens. These are the two blood parasites Hemolivia mauritanica and Hepatozoon kisrae as well as Coxiella burnetii, the causative agent of Q fever.